(untitled) (Journal of Enam Medical College, 2016)
Background: Phacoemulsification is the modern method of sight restoring surgery for cataract and it is becoming popular day by day. We planned this study to find out any significant cell loss during this procedure leading to corneal endothelial decompression. Objective: To compare the preoperative and postoperative cell counts after phacoemulsification surgery. Materials and Methods: This prospective study was carried out at the National Institute of Ophthalmology and Hospital, Dhaka from July to September, 2008 to see the corneal endothelial change after phacoemulsification. A total of 60 cases with lental opacity, who underwent phacoemulsification surgery, were studied with specular microscope. The endothelial cell count was measured with specular microscope before and after cataract surgery. Postoperative cases were followed up to one and half months after surgery. A single group of patients were studied and their preoperative and postoperative values were compared. The inclusion and exclusion criteria were maintained properly. Results: The mean preoperative endothelial cell count was 2745.35 ± 395.27 (SD) per mm2 which gradually decreased to 2545.23 ± 348.83 (SD) per mm2 at the end of one and half months after surgery; mean cell loss was 200.12 ± 46.44 (7.29%). Conclusion: This study reveals that a moderate loss of endothelial cell after phacoemulsification does not hamper the corneal transparency and visual function as depicted from visual acuity records in follow-up periods, provided the endothelium is healthy and the number is above the threshold limit. J Enam Med Col 2016; 6(3): 134-139